Facial Expression Recognition Using Euclidean Distance Method - Anagha Sharad Dhavalikar; Ramesh K. Kulkarni (Journal of Telematics and Informatics, 2014)
Facial expression recognition is found to be useful for emotion science, clinical psychology and pain assessment. In the proposed method, the face detection algorithm involves lighting compensation for getting uniformity on face and morphological operations for retaining the required face portion. After retaining the face portion in the image, the facial features like eyes, nose, and mouth are extracted using AAM (Active Appearance Model) method. For automatic facial expression recognition, simple Euclidean Distance method is used. In this method, the Euclidean distance between the feature points of the training images and that of the query image is compared. Based on minimum Euclidean distance, output image expression is decided.